Acoustic emission analysis of the compressive deformation of iron foams and their biocompatibility study - Park, Hyeji; Hong, Kicheol; Kang, Jin Soo; Um, Teakyung; Knapek, Michal; Minárik, Peter; Sung, Yung-Eun; Máthis, Kristián; Yamamoto, Akiko; Kim, Hyun-Kyung; Choe, Heeman (Materials science & engineering. C, Materials for biological applications, 2019)
We synthesized Fe foams using water suspensions of micrometric Fe2O3 powder by reducing and sintering the sublimated Fe oxide green body to Fe under 5% H2/Ar gas. The resultant Fe foam showed aligned lamellar macropores replicating the ice dendrites. The compressive behavior and deformation mechanism of the synthesized Fe foam were studied using an acoustic emission (AE) method, with which we detected sudden localized structural changes in the Fe foam material. The evolution of the deformation mechanism was elucidated using the adaptive sequential k-means (ASK) algorithm; specifically, the plastic deformation of the cell struts was followed by localized cell collapse, which eventually led to fracturing of the cell walls. For potential biomedical applications, the corrosion and biocompatibility characteristics of the two synthesized Fe foams with different porosities (50% vs. 44%) were examined and compared. Despite its larger porosity, the superior corrosion behavior of the Fe foam with 50% porosity can be attributed to its larger pore size and smaller microscopic surface area. Based on the cytotoxicity tests for the extracts of the foams, the Fe foam with 44% porosity showed better cytocompatibility than that with 50% porosity.
Keywords: Animals; pevnost v tlaku; buněčné linie; viskoelastické látky; akustika; biokompatibilní materiály; železo; Fibroblasts; poréznost; koroze; železité sloučeniny; Mice; fibroblasty; myši; Viscoelastic Substances; Cell Line; Porosity; Corrosion; Biocompatible Materials; Materials Testing; X-Ray Diffraction; Compressive Strength; Acoustics; difrakce rentgenového záření; Iron; Electrochemistry; testování materiálů; zvířata; Ferric Compounds; elektrochemie